2020
DOI: 10.1016/j.cellsig.2020.109720
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor inhibits the growth of hepatocellular carcinoma cells via regulating HULC/miR-134-5p/FOXM1 axis

Abstract: Background Highly upregulated in liver cancer (HULC), the specifically overexpressed long non-coding RNA (lncRNA) in human hepatocellular carcinoma (HCC), can promote the growth and metastasis of HCC cells. Therefore, it will be benefit to HCC treatment by effectively downregulating HULC. Liver X receptor (LXR), a member of nuclear receptor superfamily, exerts anti-tumor effects on various human malignancies including HCC. However, it is unclear whether the anti-HCC function of LXR is involved in the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…HULC knockdown increased the chemosensitivity to oxaliplatin through the repression of cell growth and the acceleration apoptosis in HCC cells. Further analysis confirmed its mode of action through the regulation of the miR-383-5p/vesicle-associated membrane protein-2 axis, the miR-377-5p/HIF-1α pathway, and the miR-134-5p/FOXM1 axis [41,42]. Emerging evidence provides new insights on the role of other lncRNAs in HCC development, such as NEAT1, ANRIL, SNHG1, or H19 [36,69].…”
Section: Non-coding Rnasmentioning
confidence: 79%
See 1 more Smart Citation
“…HULC knockdown increased the chemosensitivity to oxaliplatin through the repression of cell growth and the acceleration apoptosis in HCC cells. Further analysis confirmed its mode of action through the regulation of the miR-383-5p/vesicle-associated membrane protein-2 axis, the miR-377-5p/HIF-1α pathway, and the miR-134-5p/FOXM1 axis [41,42]. Emerging evidence provides new insights on the role of other lncRNAs in HCC development, such as NEAT1, ANRIL, SNHG1, or H19 [36,69].…”
Section: Non-coding Rnasmentioning
confidence: 79%
“…Regulation of mitochondrial metabolism [38] HULC Growth of liver cancer stem cells [39] Chemosensitivity of anti-cancer drug oxaliplatin inhibition [40] Regulation of miR-383-5p/vesicle-associated membrane protein-2 pathway; miR-377-5p/HIF-1α pathway and miR-134-5p/FOXM1 pathway [41,42] On the contrary, hypermethylation may disturb the function of another group of genes. One of the signaling pathways affected by hypermethylation is the WNT/β-catenin signaling.…”
Section: Malat1mentioning
confidence: 99%
“…Additionally, miR-134 was found to have a connection to liver cancer. He et al ( 26 ) found that miR-134 targets FOXM1 to inhibit HCC cell proliferation. In this study, we observed that propofol promoted caspase-3 activity, while miR-134 deficiency induced by transfecting miR-134 inhibitor reserved this situation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, FOXM1 has been proven to play a promoting role in a variety of tumors, including HCC [186][187][188]. Therefore, LXR can inhibit the growth of HCC cells by reducing HULC, increasing miR-134-5p and reducing FOXM1 [185].…”
Section: Lipid Metabolism Influences Lncrna Expressionmentioning
confidence: 96%
“…He et al found that LXRα can bind to the lncRNA HULC promoter region and inhibit the transcriptional activity of the HULC gene promoter. HULC can inhibit miR-134-5p targeting the 3'-UTR of FOXM1 to upregulate the expression of FOXM1 [185]. In previous studies, FOXM1 has been proven to play a promoting role in a variety of tumors, including HCC [186][187][188].…”
Section: Lipid Metabolism Influences Lncrna Expressionmentioning
confidence: 98%